Al-'Aql 'Inda Az-Zamakhshari Fi Tafsir Al-Kashaf. - Irfan Fahrizal (Jurnal Hikmatuna, 2016)
The discussion about the relationship between the intellect and the soul has been a subject of dialogue that has been ongoing since ancient times until today. Human beings are rational creatures that God has honored and bestowed with numerous blessings. Humans are capable of recognizing and being aware of many of God's favors, and they are encouraged to be humble and submissive to God. The Quran addresses the intellect, thoughts, and existence of humans, proclaiming that God has granted them the ability to hear, see, and comprehend. The intellect is the essence of human life and distinguishes humans from animals. Additionally, in logic, humans are recognized as beings capable of speech, and it is understood that the intellect encompasses everything within the heart. The Mu'tazilah doctrine presents the intellect as the source of true knowledge from God. On the other hand, the Ash'ari school strikes a balance between the intellect and revelation. Hence, the intellect is accepted in matters related to theology. Regarding matters related to the Hereafter, they give priority to revelation, specifically auditory revelations. Among the interpreters who delve into the intellect is Az-Zamakhshari, who extensively explored the fields of jurisprudence and rational schools of thought in theology. They interpret the verses with outstanding expertise, providing insights into the realities of the revelations and the various perspectives. Through this study, it becomes evident that Az-Zamakhshari's understanding of the intellect in his interpretation of Al-Kashaf is what is perceived by those who comprehend and consider the verses that God has created as a significant indication of His immense power and astonishing wisdom. Az-Zamakhshari recognized the power of the intellect, which consists of four matters: knowledge of God, knowledge of the obligation to be grateful to Him, knowledge of good and evil, and knowledge of the obligation to embrace the good and avoid the evil. The functions of the intellect include analysis, reflection, remembrance, and contemplation. Its benefits include stimulating human thinking, reasoning, and contemplating the signs of the universe. However, the intellect is limited when it comes to matters related to the soul, the Hour, Paradise, Hell, and the afterlife. The intellect acknowledges the relationship between knowledge and power and acknowledges the absolute certainty of the Day of Resurrection since God has commanded us to believe in it. Keywords: intellect, Az-Zamakhshari, interpretation of Al-Kashaf, famous interpretation.